Exploring Transport Behavior in Hybrid Perovskites Solar Cells via Machine Learning Analysis of Environmental-Dependent Impedance Spectroscopy - Kim, Dohyung; Muckley, Eric S.; Creange, Nicole; Wan, Ting Hei; Ann, Myung Hyun; Quattrocchi, Emanuele; Vasudevan, Rama K.; Kim, Jong H.; Ciucci, Francesco; Ivanov, Ilia N.; Kalinin, Sergei V.; Ahmadi, Mahshid (Advanced Science, 2021)
Hybrid organic–inorganic perovskites are one of the promising candidates for the next-generation semiconductors due to their superlative optoelectronic properties. However, one of the limiting factors for potential applications is their chemical and structural instability in different environments. Herein, the stability of (FAPbI3)0.85(MAPbBr3)0.15 perovskite solar cell is explored in different atmospheres using impedance spectroscopy. An equivalent circuit model and distribution of relaxation times (DRTs) are used to effectively analyze impedance spectra. DRT is further analyzed via machine learning workflow based on the non-negative matrix factorization of reconstructed relaxation time spectra. This exploration provides the interplay of charge transport dynamics and recombination processes under environment stimuli and illumination. The results reveal that in the dark, oxygen atmosphere induces an increased hole concentration with less ionic character while ionic motion is dominant under ambient air. Under 1 Sun illumination, the environment-dependent impedance responses show a more striking effect compared with dark conditions. In this case, the increased transport resistance observed under oxygen atmosphere in equivalent circuit analysis arises due to interruption of photogenerated hole carriers. The results not only shed light on elucidating transport mechanisms of perovskite solar cells in different environments but also offer an effective interpretation of impedance responses.
Keywords: Equivalent circuit model; Impedance spectroscopy; Nonnegative matrix factorization; Optoelectronic properties; Photogenerated hole carriers; Recombination process; Structural instability; Transport resistance; distribution of relaxation time; hybrid perovskites; impedance spectroscopy; machine learning; solar cells